Demographic parameters and reproductive performance of the assassin bug Sycanus dichotomus Stal. fed on mealworm Tenebrio molitor L. - Ibrahim Yusof, Othman Mohd Fairuz, (N/A, 2011)
Demographic parameters and reproductive performance of the assassin bug Sycanus dichotomus Stal. fed on mealworm Tenebrio molitor L. by Ibrahim Yusof, Othman Mohd Fairuz,